Influence of growth conditions on cell surface hydrophobicity of Candida albicans and Candida glabrata. - Hazen, K C (Infect Immun, 1986)
The effect of cultural conditions on cell surface hydrophobicity of Candida albicans and Candida glabrata was tested. C. albicans cells grown at room temperature were more hydrophobic than cells grown at 37 degrees C. No consistent pattern was observed with C. glabrata. Relative hydrophobicity was found to vary with the growth phase and growth medium for both species. The implications for pathogenesis studies are discussed.